1999
DOI: 10.1016/s1010-7940(98)00296-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of neurological morbidity after coronary artery bypass surgery

Abstract: Peripheral vascular atherosclerosis, neurological pathology, aorta-pathology, the occurrence of a perioperative myocardial infarction and the time cohort 1993-1995 are identified as independent risk factors for neurological complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Several demographic risk factors behind stroke have been suggested in previous studies [3,16]. CPB exposure has also been addressed, in relation to potential OPCAB benefits [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several demographic risk factors behind stroke have been suggested in previous studies [3,16]. CPB exposure has also been addressed, in relation to potential OPCAB benefits [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be speculated that many of these risk factors depend on how the stroke variable was defined and handled. In the majority of previous studies, including large cohort analyses, stroke was not subdivided into early and delayed form [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of plaque rupture and mobilization is evident, since neurological complications after ECC in cardiosurgical patients range from 1% to 10% (Bucerius et al, 2003;Janssen et al, 1999), dependent on the type of surgery, and have been reported to reach up to 16% in high risk patients (Wolman et al, 1999). Arteriosclerotic embolism is a major cause of operative stroke, and therefore the influence of different perfusion techniques should be considered.…”
Section: Pulsatile Ecc and Rupture Of Arteriosclerotic Plaquesmentioning
confidence: 99%
“…Incidence of neurologic side effects related to cardiac surgery has been reported to be 1.4% to 6% [1][2][3][4] and can reach up to 9% in patients aged over 75 years, 5,6 or up to 16% when high preoperative risk factors are present. 7,8 In addition, neuropsychological dysfunction may occur in up to 50% of patients.…”
mentioning
confidence: 99%
“…7,8 In addition, neuropsychological dysfunction may occur in up to 50% of patients. 1,3,9 Cognitive impairment, usually reversible, can affect immediate or late visual or verbal memory, attention, calculation, or processing information speed. In certain cases, cognitive decline persists 5 to 10 years after the surgical procedure.…”
mentioning
confidence: 99%